2012
DOI: 10.1063/1.4719538
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear, electrocatalytic swimming in the presence of salt

Abstract: A small, bimetallic particle in a hydrogen peroxide solution can propel itself by means of an electrocatalytic reaction. The swimming is driven by a flux of ions around the particle. We model this process for the presence of a monovalent salt, where reaction-driven proton currents induce salt ion currents. A theory for thin diffuse layers is employed, which yields nonlinear, coupled transport equations. The boundary conditions include a compact Stern layer of adsorbed ions. Electrochemical processes on the par… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
118
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(120 citation statements)
references
References 67 publications
2
118
0
Order By: Relevance
“…For bimetallic nanorods, the addition of sub-millimolar amounts of salt can significantly reduce the swimming velocity [14,31]. This is consistent with self-electrophoresis [14,16,18,32]. However, experiments have also found that addition of some salts (e.g.…”
supporting
confidence: 63%
“…For bimetallic nanorods, the addition of sub-millimolar amounts of salt can significantly reduce the swimming velocity [14,31]. This is consistent with self-electrophoresis [14,16,18,32]. However, experiments have also found that addition of some salts (e.g.…”
supporting
confidence: 63%
“…(ii) For the self-electrophoretic swimmers, we consider the standard Au-Pt model of Refs. [26,[30][31][32], in which reactions at the surface produce and reduce an ionic species. This sets up a current of charged solutes and an electric field which induces motion of the swimmer which has a surface charge σ.…”
Section: Finite Element Simulationsmentioning
confidence: 99%
“…However, the solute species have long-ranged electrostatic interactions, which necessitates the introduction of the Poisson equation. The slip-layer approximation can still be made, but only for high salt concentrations [23,31]. A solution for low salt concentrations can also be found [32].…”
Section: Appendix B: the Self-electrophoretic Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…(8), for the dependence of the velocity on a physical controlling parameter, such as concentration, since nonlinear dependencies have been measured [9,28,[38][39][40] and predicted [9,[26][27][28] for a variety of motor propulsion mechanisms. Figure 7(a) shows the contour map of the normalized long-time effective diffusivity calculated from Eq.…”
Section: Maximum Of Effective Diffusivitymentioning
confidence: 99%